2018
DOI: 10.1016/j.celrep.2018.01.090
|View full text |Cite
|
Sign up to set email alerts
|

A Cell-Intrinsic Interferon-like Response Links Replication Stress to Cellular Aging Caused by Progerin

Abstract: SUMMARYHutchinson-Gilford progeria syndrome (HGPS) is a premature aging disease caused by a truncated lamin A protein (progerin) that drives cellular and organismal decline. HGPS patient-derived fibroblasts accumulate genomic instability, but its underlying mechanisms and contribution to disease remain poorly understood. Here, we show that progerin-induced replication stress (RS) drives genomic instability by eliciting replication fork (RF) stalling and nuclease-mediated degradation. Rampant RS is accompanied … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

7
107
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 102 publications
(132 citation statements)
references
References 47 publications
7
107
0
Order By: Relevance
“…Our previous studies revealed that calcitriol treatment ameliorates many of the aging phenotypes in progerin‐expressing cells, including DNA damage and RS . Here, we find that pre‐treatment of HDFs with calcitriol for 2 days prior to induction of progerin completely prevents the RFI observed 48 h after doxycycline treatment (Figure 1C).…”
Section: Resultssupporting
confidence: 69%
See 4 more Smart Citations
“…Our previous studies revealed that calcitriol treatment ameliorates many of the aging phenotypes in progerin‐expressing cells, including DNA damage and RS . Here, we find that pre‐treatment of HDFs with calcitriol for 2 days prior to induction of progerin completely prevents the RFI observed 48 h after doxycycline treatment (Figure 1C).…”
Section: Resultssupporting
confidence: 69%
“…To understand the molecular mechanisms underlying RS in progerin‐expressing cells, and the mechanisms responsible for the rescue by calcitriol, we monitored the levels of factors with a known role in RF stability and DNA repair. First, we re‐analyzed our published RNAseq studies performed in HGPS patient derived fibroblasts proliferating in culture for 3 months (accession number: GSE97986) to monitor levels of expression of DNA repair/replication factors. This analysis revealed downregulation of a variety of factors in the BRCA pathway with respect to normal fibroblasts from parents of HGPS patients ( Figure 2A).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations